Preparation of antibacterial keratin fabrics via UV curing and click chemistry. Issue 85 (30th August 2016) - Hu, Yi; Wang, Wei; Yu, Dan
Abstract : A clean and cost-effective surface modification method of keratin fabrics was proposed by UV curing and thiolene click reaction. Abstract : A clean and cost-effective surface modification method of keratin fabrics was proposed by UV curing and thiolene click reaction. This method introduced a novel water-soluble photoinitiator 2, 2-dimethylol propionic acid used in the UV curing process to avoid pollution caused by organic solvents. Pretreatment with tris(2-carboxyethyl)phosphine as a mild reducing agent was carried out to produce thiol groups on the surface of biological substrates. Then, diallyl dimethyl ammonium chloride was grafted onto the surface of the pretreated substrate through thiol–ene click chemistry under UV irradiation. The reaction was confirmed by SEM, FTIR spectra, TGA and XPS analysis. The experimental results demonstrate that this reaction can impart keratin fabrics with excellent antibacterial activity, antistatic properties and hydrophilicity.